The outcomes of Industry Collaboration Programme (ICP) that affect technical skills and knowledge development amongst local industries - Safari, Zailani (2022)
This thesis is about research on the impact of the Industry Collaboration Program (ICP) implementation in Malaysia to local industry players, focusing on the aspects of technical competencies and knowledge development. ICP is initiative formulated by the Government of Malaysia based on countertrade mechanism practiced globally. It is a mandatory requirement to be carried out by the suppliers who been awarded with contracts by the Government of Malaysia (GOM), that the value is above a specific threshold. It is currently become part and parcel of the procurement policy imposed by the GOM, which is intended to support local industry capabilities development that contribute to local economic growth. Nevertheless, the outcomes of ICP initiative in Malaysia was never measured systematically, so that it could be gauged objectively. Hence, this research is carried out to gauge the outcomes of the ICP implementations to provide an objective assessment specifically on those programs related to transportation industry (land, maritime and aerospace) in Malaysia. In carrying out assessments for this research, the ICP implementation outcomes was viewed from the aspect of technical competency development. It is envisioned that human capital development is to be key to successful program implementation in various countries that practiced initiatives similar to ICP. In analysing the ICP implementation outcomes in Malaysia, the researcher has systematically collected a set of data using a mixed method (quantitative and qualitative) leveraging on the Adaptive Capacity (AC) approach. The data were obtained from local industry players that are participating or has participated as ICP recipients. The research analysis was done based on an AC theoretical model and its validity was tested statistically using the SPSS-AMOS application. The researcher has developed seven (7) hypotheses around the theoretical model. The hypotheses test outcomes and the findings from the survey were then triangulated with obtained qualitative data to confirm their correctness. Based on the analysis, the researcher has conclusively carried out the assessment and found eleven (11) issues and eight (8) gaps related to the current ICP implementation in Malaysia. In addressing the gaps and issues, the researcher has proposed five (5) recommendations that could be used as inputs to strengthen the current ICP policy and implementation framework. The recommendations shall be shared with the Malaysian ICP Authority to resolve current issues and challenges, in particular those which are related to human capital development and technology development approaches that leverage on ICP. Further, the new knowledge is envisaged to able to contribute to the processes betterment to achieve the intended ICP impact to support national technology and economy development.